(untitled) (Bangladesh Journal of Botany, 2008)
Essential oil of fresh matured leaves of Lantana camara L. growing in Bangladesh were analyzed by GC-MS technique. Sixty two compounds were identified in the oil. The major constituents identified include caryophyllene (13.57%), α-caryophyllene (11.76%), germacrene D (10.88%), isocaryo-phyllene (9.59%), Î³- muurolene (6.85%) and Î³-elemene (5.65%). Â Key words: Lantana camara, Essential oil, Caryophyllene DOI = 10.3329/bjb.v36i2.1513 Bangladesh J. Bot. 36(2): 193-194, 2007 (December)